Nexus of Assimilation Between Indian and Chinese Bourses - Vevek , S; Selvam , M; Ganapathy, S (Journal of Ecohumanism, 2024)
This paper examines the correlation between India’s NIFTY 50 and China’s Shanghai Stock Exchange (SSE) Composite subsequent to the Yuan’s devaluation on June 11, 2015. The study employs statistical and economic approaches to assess three stages during a 12-year period from 2005-2006 to 2016-2017. The literature study rigorously analyzes stock market volatility and the merger of growing Asian markets with developed markets. The research presents two hypotheses to evaluate the long-term correlation and causality between the two indexes. Daily closing prices are analyzed during event windows established by the devaluation event. The findings indicate an inverse correlation between NIFTY 50 and SSE Composite during event periods, with Augmented Dickey-Fuller (ADF) tests validating stationarity and a co-integrated connection (I(1)). The Johansen Co-integration test demonstrates a long-term proportional relationship, but Granger Causality tests show both unidirectional and bidirectional causal relationships over time. The Vector Error Correction Model (VECM) research reveals a reciprocal connection, indicating that NIFTY 50 achieves equilibrium restoration more rapidly. The results enhance comprehension of the amalgamation of the Indian and Chinese stock markets.